The Impact of Social Proof and Price Discounts on Consumer Purchase Behavior: Mediating and Moderating Effects - Sehrish Batool (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The study specifically aims to evaluate the direct effects of social proof and price discounts, the mediating role of consumer perceptions between these factors and purchase behavior, and the moderating role of purchase urgency on these relationships. The research adopts a quantitative methodology grounded in a positivist philosophy, which emphasizes objective measurement and statistical analysis. The population for this study comprises online shoppers, with a known population size. A stratified random sampling technique was employed to ensure diverse representation, resulting in a sample size of 540 respondents. Data were collected using a structured survey, and analysis was conducted using SPSS and Excel. The findings reveal that social proof significantly impacts consumer purchase behavior. Positive reviews, ratings, and customer testimonials enhance consumer trust and influence purchase decisions. Similarly, price discounts were found to have a substantial effect, as they create a perception of value and urgency, encouraging consumers to make immediate purchases. Furthermore, the mediating role of consumer perceptions was significant, amplifying the effects of social proof and price discounts on purchase behavior. The moderating role of purchase urgency further strengthened these relationships, indicating that urgency intensifies the impact of both social proof and discounts. This study highlights the importance of integrating social proof and strategic pricing into marketing strategies to boost consumer engagement and drive sales.